2016
DOI: 10.1016/j.jaad.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib, an oral Janus kinase inhibitor, for the treatment of chronic plaque psoriasis: Long-term efficacy and safety results from 2 randomized phase-III studies and 1 open-label long-term extension study

Abstract: Oral tofacitinib demonstrated sustained efficacy in patients with psoriasis through 2 years, with 10 mg BID providing greater efficacy than 5 mg BID. No unexpected safety findings were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
98
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 15 publications
14
98
1
6
Order By: Relevance
“…Safety data for tofacitinib is derived from large clinical trials in RA and psoriasis 4245 , and data for ruxolitinib are from clinical trials in myelofibrosis and polycythemia vera 4648 .…”
Section: Safety Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Safety data for tofacitinib is derived from large clinical trials in RA and psoriasis 4245 , and data for ruxolitinib are from clinical trials in myelofibrosis and polycythemia vera 4648 .…”
Section: Safety Datamentioning
confidence: 99%
“…Increases in total cholesterol, LDL cholesterol, and HDL cholesterol have been reported with tofacitinib and ruxolitinib therapy, but are typically mild 1,45,51,52 . Patients treated with JAK inhibitors do not appear to have an increased risk of major adverse cardiac events or stroke 42,45,53,54 .…”
Section: Safety Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy and safety of tofacitinib 5 and 10 mg twice daily (b.i.d.) in patients with moderate to severe chronic plaque psoriasis has been demonstrated in global phase 3 trials of up to 56 weeks’ duration, and in a long‐term extension (LTE) study with efficacy end‐points reported through 24 months and safety reported over 33 months of exposure . The efficacy and safety of tofacitinib has also been studied in several other immune‐mediated inflammatory diseases, including rheumatoid arthritis, psoriatic arthritis (NCT01877668, NCT01882439, NCT01976364), ankylosing spondylitis, Crohn's disease (NCT01393626, NCT01393899, NCT01470599) and ulcerative colitis …”
Section: Introductionmentioning
confidence: 99%